A Comparative Study of Two Different Methods for Determining the Root Canal Working Length - Moradi, Saeed; Javidi, Maryam; Rashed, Roozbeh; Raziee, Leila (Iranian Endodontic Journal, 2010)
INTRODUCTION: Success in endodontic treatment depends on various factors. Among the most important factors, appropriate preparation of the root canal system and keeping periapical region intact as much as possible could be mentioned. These are achieved by determining the penetration depth of the instruments into the canal i.e. the working length. Several methods are introduced for working length determination. The most popular techniques in this regard are the use of conventional radiography and electronic apex locators. A new type of apex locator is the Root ZX. The purpose of this study was to compare the accuracy rate of Root ZX apex locator with the conventional radiography. MATERIALS AND METHODS: The working length of thirty extracted single rooted teeth were determined by the means of the Root ZX and conventional radiography then compared with the actual working lengths measured by the stereomicroscope. RESULTS: The results showed there was statistically significant difference between the length determined by the Root ZX and stereomicroscope. In addition, the radiographic and stereomicroscopic working lengths had statistically significant differences as well. There was also significant difference between the lengths measured by the Root ZX and radiography. CONCLUSION: It is recommended to use the Root ZX and radiography both together to reach the most accurate working length.